Peran Peter William Hofland dalam Mengelola Tanah Partikelir Pamanoekan en Tjiasem Landen Subang Tahun 1802-1874 - Sopianna, Pian; Faturrachman, Muhammad Noer; Mardani, Mardani (Historia Madania: Jurnal Ilmu Sejarah, 2020)
This article deals with the role of a Peter William Hofland in developing the lands of Pamanoekan en Tjiasem in Subang Regency. William was considered to have successfully developed the lands, particularly in running the plantation business within the area of Subang. This study uses historical methods, namely heuristics, criticism, interpretation, historiography. Historically, William managed the land of Pamanoekan en Tjiasem since 1840 until his death in 1972. Within a period of 32 years, he had succeeded in developing the land of land in his territory namely Pamanoekan en Tjiasem Landen which is now known as Subang Regency. Keywords: Land Policy, Peter William, Plantation Business